Assessment of efficiency in basic and secondary education in Tunisia: A regional analysis. (November 2016) - Ramzi, Sourour; Afonso, António; Ayadi, Mohamed
Highlights: The absence of significant effect of school resources on the efficiency of governorates in terms of 2nd cycle and secondary education in Tunisia. The only factor that influences the efficiency level of education is the output variable non-doubling in the 9th year. The disequilibrium between East regions and other regions of Tunisia in terms of education efficiency can be explained by the disparity of the socioeconomic factors characterizing each region. The efficiency level in basic and secondary education is positively influenced the level of employment and negatively influenced by the degree of extreme poverty. Abstract: To determine the factors enhancing the efficiency of basic and secondary education in 24 governorates of Tunisia in 1999, 2003, 2006 and 2008, we apply a non-parametric approach, Data Envelopment Analysis (DEA) to multi-inputs and multi-outputs. Physical resources used in the study are: the number of classes per 100 students and the number of schools per million inhabitants. Human and financial resources are described by the number of teacher per 100 students and education spending per student respectively. The output measures include the success rate of baccalaureate exam and the rate of non-doubling in the 9th year. Our results show the absence of significant relationship between school resources and student performance. The output variable, non-doubling rate in the 9th year is the only factor able to influence the efficiency level of governorates in terms of 2nd cycle of basic education and secondary education. By regressing efficiency scores on non-discretionary variables, we find that inefficiency in education is strongly related to poverty within governorates.